ANALISIS POLA PEMBERANTASAN KORUPSI DALAM PENGADAAN BARANG/JASA PEMERINTAH - Amiruddin Amiruddin (Jurnal Kriminologi Indonesia, 2012)
The pattern of corruption eradication effort in procurement of goods and services has a spesific characteristic and differs from other general patterns of corruption eradication various aspects of law in procurement of goods and services are dominated by elements regarding administrative law and civil law. Therefore, pattern of its violations also exists in those two areas of laws. Hence, the eradication strategy shall prioritize the enforcement of administrative law which has main function to provide a sustainable controlling element as preventive factor without neglecting the repressive action. The repressive action is manifested through punishment as an ultimatum remedium if toward corruption in the procurement of goods and services.